Percepção dos pais sobre o ambiente e tempo em atividade física ao ar livre de pré-escolares de baixa renda - Souza, Cleene Tavares de (2021)
Introducion: Outdoor physical activities (OPA) contribute to children's development. However, it is assumed that in preschool children, parents' perception of the environment may be related to the shorter or longer time spent in these activities. Objective: to analyze the association between parents' perception of the environment and OPA outside school in low-income preschoolers, considering possible sociodemographic correlates. Methods: 129 preschoolers aged 3 to 5 years (4.4 years ± 0.7 years, 50% boys) participated in the study. The parents' perception of the environment and the children ́s time in OPA were evaluated through a questionnaire, applied in a face-to-face interview with the parents. Socio-demographic data such as gender, age, mother's education, family income and presence of siblings were informed by parents during the interview. To analyze the associations between parents' perception of the environment and OPA, logistic regression was used, considering a significance level of 95% for OPA as outcome during the week and at the weekend. The data were analyzed using the Statistical Package for Social Sciences (SPSS; version 21.0). Results: A total of 76.9% of the preschoolers had < 2 hours/day in OPA during the week. At the weekend, 65.9% reached > 2 hours in OPA. Parents' perception of no traffic safety (OR: 0.39; p: 0.03) showed higher chances for a shorter children ́s time in OPA during the week, and at the weekend (OR: 0.46; p:0.04). Moreover, parents’ perception of the lack of places to walk (OR: 0.33; p: 0.02) and night safety (OR: 0.36; p: 0.04) is associated to a more likely to achieve less time in OPA during the week. After adjustments for sociodemographic confounders, the perception of no traffic safety (OR: 0.26; p: 0.01) and of places to walk in OPA during the week. After adjustments for sociodemographic confounders, the perception of no traffic safety (OR: 0.26; p: 0.01) and places to walk (OR: 0.15; p: 0.01) were predictors of the shortest time in OPA of preschoolers during the week. Conclusion: Parents' perception of lack of traffic safety and places to walk were associated with less time in OPA in low-income preschoolers, especially during the week days.